2023
DOI: 10.3390/app132212220
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Dynamic Response of Helical Pile in Viscoelastic Foundation Considering Shear Deformation

Xiaoyan Yang,
Chaozhe Wang,
Sheng Cao
et al.

Abstract: Helical piles are a new type of pile that has good application prospects, and researchers have carried out an in-depth investigation into their vertical uplift and compressive bearing capacity. However, there is relatively little research on the dynamic bearing characteristics of helical piles. Therefore, the lateral vibration of a helical pile embedded in the viscoelastic foundation is systematically studied in this article. Utilizing the equivalent stiffness method to transform a helical pile into a cylindri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Khatri et al [16] proposed a formula for the ultimate uplift capacity of piles in cohesive soil where the undrained cohesion linearly increases with depth. Based on the Winkler foundation model and Timoshenko beam theory, Yang et al [17] established a lateral vibration model of screw piles considering shear deformation and derived analytical solutions for the lateral dynamic displacement, bending moment, and shear force. Patra and Pise [18] proposed a simplified method to predict the ultimate uplift capacity of pile groups, taking into account factors such as the buried length-to-diameter ratio of the group pile and the pile spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Khatri et al [16] proposed a formula for the ultimate uplift capacity of piles in cohesive soil where the undrained cohesion linearly increases with depth. Based on the Winkler foundation model and Timoshenko beam theory, Yang et al [17] established a lateral vibration model of screw piles considering shear deformation and derived analytical solutions for the lateral dynamic displacement, bending moment, and shear force. Patra and Pise [18] proposed a simplified method to predict the ultimate uplift capacity of pile groups, taking into account factors such as the buried length-to-diameter ratio of the group pile and the pile spacing.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that spacing the anchors at approximately three times the diameter of the largest helix did not lead to a significant decrease in the uplift capacity of each individual anchor [41]. The characteristics of grouped helical anchors under lateral static [21,35,[42][43][44][45] and dynamic loads [46][47][48][49][50] have been studied. In a study conducted by Venkatesan Vignesh, the uplift and lateral behavior of group piles installed in soft clay soil was studied using a finite element and 1 g model experiment.…”
Section: Introductionmentioning
confidence: 99%